Ferroelectric glass-ceramics from the PbO-GeO2-Nb2O5 system - Pengpat K. (2014)
Glass-ceramics with compositions Pb5Ge3O11-xPbNb2O6 (PG-xPN) where x equals 0.0, 0.5, 1, 2 and 3, and other selected compositions from the PbO-GeO2-Nb2O5 system, have been prepared using the conventional melt-quench method. Most of the quenched melts devitrified on cooling and gave fragile samples. The x = 0.5 (PGN2) sample formed a robust solid which contained the ferroelectric phase Pb5Ge3O11 and the pyrochlore phase Pb2Nb2O7. Glass formation was improved by replacing some Nb2O5 by GeO2. Scanning electron micrographs of cross-sections of the x = 0.5 sample showed surface crystallisation of the PG phase with a-axis orientation. The PN phase was distributed randomly in the sample. Heating the sample at 667 °C for 48 h enhanced the surface orientation of this PG phase. After poling the heat treated sample, using an electric field of up to 25 kV/cm, a ferroelectric hysteresis loop could be obtained at room temperature with Ps = 1 μC/cm2. The Curie point of this PGN2 sample was found to be ∼166 °C. © 2003 Elsevier Ltd. All rights reserved.